PERSONAL BRANDING REYNALTO PRIYAN PRADHANA MELALUI INSTAGRAM REYDECAL DALAM PENINGKATAN PENJUALAN - Muhammad Dias Ricardo; Djudjur Luciana Radjagukguk (Universitas Nasional, 2020)
The development of technology today has resulted in the development of aspects of human life, the number of media that have emerged in society. Instagram is a social media that the Indonesian people enjoy doing. Instagram can also build a brand and can build personal branding for its users. The purpose of this study is to identify and analyze the personal branding of Reynalto Priyan Pradhana through reydecal diagrams in increasing sales. The method used is descriptive qualitative by collecting data through interviews, observation and documentation. The results of Reynalto Priyan's research use eight elements of personal branding formation, namely: a) Specialization in which Reynalto is a sports motorbike lover, so it is not surprising that Reynalto understands several motorcycle parts; b) Leadership, Reynalto is mentioned as a big branding factor that makes Reydecal's name inseparable from himself; c) Personality means that Reynalto has a simple and straightforward appearance, Reynalto is also a person who is friendly to all circles; d) The difference is that on Instagram Reydecal, Reynalto shows differences from other decal business owners; e) It appears that as a big brand owner, Reynalto has unique characteristics in order to compare Reydecal to be better known for himself; f) Unity means that Reynalto's moral ethics and attitude are very much in line with what he wants to form with the reydecal brand; g) Persistence that from 2014 to 2020, Reydecal routinely uploads photos and videos with content with Reynalto; and h) A good name, namely Reynalto, who often thanked customers through captions, Instagram stories or in person.